Effect of contrast agent viscosity and injection flow velocity on bolus injection pressures for peripheral venous injection in first-pass myocardial perfusion studies - Walsh, Edward G.; Doyle, Mark W.; Anayiotos, Andreas (My University, 2002)
Myocardial perfusion imaging using Gd contrast agents is typically performed with bolus injections of the contrast agent using a power injector to provide for consistent and sufficiently rapid injection rates for all patients. For protocols in which a peripheral venous injection is called for (e.g. antecubital vein) injection catheters of 18 ga are used where vessel geometry permits. In some patients, particularly women with smaller veins, 20 and 22 ga catheters are used. The effect of catheter size and pressure tubing length can result in high injection pressures that occasionally cause leakage or connector failure. The viscosity of the contrast agent also impacts injection pressure. In this study, a simulation of the injection pathway was constructed with time resolved pressures measured at two points in the pathway. Pressure drops were calculated for a typical MR perfusion injection protocol.
Keywords: Catheterization; Contrast media (Diagnostic imaging); Viscosity; Magnetic resonance imaging